From anecdote to evidence: dispelling myths in bodybuilding and physique sports - Roberts, B. M.; Buckner, S. L.; Colenso-Semple, L. M.; Conlin, L. A.; Church, D. D.; Campbell, B. I.; De Souza, E. O.; Gonzalez, A. M.; Helms, E. R.; Newmire, D. E.; Pearson, J. R.; Tinsley, G. M.; et al. (Strength and Conditioning Journal, 2026)
Bodybuilding and physique sports are often clouded by myths and misconceptions about training, nutrition, and supplements. This article examines some of the myths in the fitness community, including periodization for muscle growth, the belief that training to failure is required, and the idea that cardiovascular training impairs hypertrophy. In addition, this article covers misconceptions about nutritional strategies, such as the need for restrictive diets, the effectiveness of fasted cardiovascular training, and the importance of meal timing. The fear that women will become bulky from resistance training and the misclassification of creatine as a steroid are also addressed. Drawing on current scientific evidence, we demonstrate that progressive overload, intensity management, and flexible dieting are more effective and sustainable than other methods. Cardiovascular training, when properly integrated, does not hinder muscle growth, and women benefit from resistance training without developing excessive muscle mass. Creatine supplementation is validated as a safe and effective ergogenic aid and is distinct from anabolic steroids. By debunking and contextualizing these myths, this article provides bodybuilders and physique athletes with evidence-based training and nutrition strategies to optimize performance, support long-term health, and maximize results safely and efficiently.